Penanaman Pendidikan Karakter melalui Kegiatan Keagamaan di SMA Al-Azhar Syifa Budi Surakarta Tahun Pelajaran 2020/2021 - Qomariyah Kariem Asya, Tamimatul (AL MURABBI, 2022)
Tamimatul Qomariyah Karim Asya. O100190012. "Inculcating Character Education through Religious Activities at Al-Azhar Syifa Budi High School Surakarta". Thesis of the Master of Islamic Education Study Program. Graduate School of the University of Muhammadiyah Surakarta. Advisor I Dr. Mutohharun Jinan, M. Ag., Advisor II Dr. Muthoifin, M. Ag. The purpose of this study was to describe the cultivation of character education through religious activities at Al-Azhar Syifa Budi High School Surakarta. This research method uses a qualitative method using a case study approach. The research design applied is sociological. Research data collection techniques through observation, interviews, and documentation. The data analysis technique this in this study was through data reduction, data presentation, and data withdrawal and testing. The result of this research is that the planning of character education planting through religious activities at Al-Azhar Syifa Budi High School Surakarta has been very well coordinated. Planning for daily and annual activities is carried out before the new school year begins. Planning is made jointly by involving the research and development (R&D) team. The activities development are detailed with the person in charge and the coordinator of the activities. The implementation of character education through the cultivation of character education, religious activities carried out include reading prayers before and after learning and performing dhuha prayers, the habituation has been carried out in an orderly and good manner. Students already have a high awareness of carrying out activities at school with various consequences. Keywords: Moral Degradasi, Character Education, Religious Activities